A Systematic Literature Review: Implementasi Computational Thinking pada Pembelajaran Fisika di Indonesia - Ulil Khasanah; Supahar Supahar; Trisonia Fitria; Nia Hani Prasasti; Effendi Malik (Postgraduate, University of Mataram, 2025)
The implementation of computational thinking in learning can help students have 21st century skills. This research aims to review the implementation of computational thinking in physics learning in Indonesia. Systematic literature review research using content analysis methods was used to review articles published from 2019 to 2023. The analysis techniques used were planning, conducting and reporting. Of the 170 articles, there are 20 articles that match the focus of this research. The results of the research are the type of experimental research that is most widely used with test instruments. The research subjects were high school students. Physics materials that are often used in research are kinematics and energy and work. Computational thinking is widely integrated with learning media. The media often used by researchers is scratch. This research needs to be studied further with other inclusion criteria so that there are more references regarding the implementation of computational thinking, especially in physics learning